1996
DOI: 10.1183/09031936.96.09030535
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical evidence for extra-cellular initiation of elastase-induced bronchial secretory cell metaplasia in hamsters

Abstract: I Im mm mu un no oc cy yt to oc ch he em mi ic ca al l e ev vi id de en nc ce e f fo or r e ex xt tr ra a--c ce el ll lu ul la ar r i in ni it ti ia at ti io on n o of f e el la as st ta as se e--i in nd du uc ce ed d b br ro on nc ch hi ia al l s se ec cr re et to or ry y c ce el ll l m me et ta ap pl la as si ia a i in n h ha am ms st te er rs s ABSTRACT: The bronchus is the only region of the hamster conducting airways to develop secretory cell metaplasia after an intratracheal instillation of human neutrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Our laboratory and others have reported that proteolytic activity is required for NE-induced gene expression (12,37). In studies with airway epithelial cells, NE has been immunolocalized to the extracellular space (38). Therefore, we predict that the primary event in NEregulated gene expression is NE interaction with the epithelial cell membrane.…”
Section: Discussionmentioning
confidence: 80%
“…Our laboratory and others have reported that proteolytic activity is required for NE-induced gene expression (12,37). In studies with airway epithelial cells, NE has been immunolocalized to the extracellular space (38). Therefore, we predict that the primary event in NEregulated gene expression is NE interaction with the epithelial cell membrane.…”
Section: Discussionmentioning
confidence: 80%
“…7), suggesting a direct effect of tiotropium on NE-induced mucin production in airway epithelial cells. NE has been found to act on the epithelial cell surface [20] and activate signalling via multiple pathways, including generation of reactive oxygen species [21,22], activation of toll-like receptor 4 [23] and activation of the epidermal growth factor receptor (EGFR) [11]. Transforming growth factor-a, cleaved by NE, and reactive oxygen species, produced by NE, have been shown to activate EGFR and induce MUC5AC production in NCI-H292 cells in vitro [11].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of PKC activation by HNE is currently unknown. Because HNE is a large molecule (molecular mass Х 29.5 kDa), and because a study showed solely extracellular staining of HNE after prolonged incubation of HNE with airway epithelium (41), it is speculated that HNE exerts its function on cell membrane surface. Further studies to identify a possible HNE receptor or other cell surface molecules are needed to understand fully the actions of HNE.…”
Section: Discussionmentioning
confidence: 99%